Morphological and Molecular Characterization Of Micromycetes Associated With Seeds of Selected Cotton (Gossypium Hirsutum L.) Varieties (Bangladesh Journal of Plant Taxonomy, 2022)
A total of 14 varieties (CB1-CB14) of cotton (Gossypium hirsutum L.) seeds were collected from Cotton Research, Training and Seed multiplication Farm, Sreepur, Gazipur to detect and identify the seed borne fungi by morphological and molecular techniques. The sequence results obtained using the ITS1 and ITS4 primers were compared with NCBI GenBank and BOL database using BLAST analysis. In the present investigation, a total of 29 fungal isolates were morphologically identified from different varieties of cotton seeds, of which 19 fungal isolates were identified by molecular techniques. Among the isolated fungi, Aspergillus subramanianii, A. toxicarius, A. wentii, Penicillium aculeatum, P. citrinum, Rhizomucor sp. and Meyerozyma guilliermondii have been reported as new records for Bangladesh.Bangladesh J. Plant Taxon. 29(2): 297-312, 2022 (December)